One's Workplace, Other's Home? Work and Health of Domestic Workers in Argentina - María Fernanda Bauleo; Frank van Dijk; Katja Radon (Ubiquity Press, 2018)
Background: Domestic workers around the world work and eventually live in private homes where control of working conditions is difficult. Objective: The aim of this study was to compare working conditions and its impact on general and mental health in live-in and live-out domestic workers in Argentina. Methods: In a cross-sectional study, the Spanish version of the European Workings Condition Survey and an ad hoc questionnaire were applied to 201 domestic workers (response 94%). Twelve months' prevalence of verbal or physical workplace violence was assessed. Poor general health was defined by general health self-assessed as poor or fair. Symptoms of common mental disorders (CMD) were considered present if Goldberg's general health score was above 4. Data were analyzed using Chi square's test and logistic regression models. Findings: Live-in workers formed 66% of the participants. They were more likely to take care of the elderly, iron and cook than live-out workers. Workplace violence was reported by 17% of live-in and 24% of live-out workers (p = 0.25). Overall prevalence of poor general health was 23%; 53% reported CMD. After adjustment, violence remained a statistically significant predictor of poor general health (Odds Ratio 7.3; 95% Confidence Interval 2.8-19.1) and CMD (3.2; 1.1-9.3). Conclusions: Working conditions of live-in and live-out domestic workers are different. However, exposure to workplace violence is common in both groups and affects general and mental health.